Variação morfometrica da cabeça de bothrops atrox: aspectos comparativos entre espécimes de diferentes hábitats da região oeste do Pará - SILVA, Antônio Samuel Garcia da (Universidade Federal do Oeste do Pará, 2021)
Bothrops atrox (Viperidae) is a nocturnal venomous snake in its diet and habitat use. This species is widely distributed throughout the Amazon, inhabiting diverse habitat types such as floodplain areas, primary and secondary forests, savanas, and degraded areas. Studies have shown variation in the composition of venom in flooded forest specimens of floodplain, which is possibly an adaptation to types of prey in these areas. The availability and composition of prey are also expected to cause morphometric variations, especially determined by characters that are measured in the head. The objective of this study was to analyze the morphometric characteristics of Bothrops atrox venom head and glands among specimens of the different habitats of the western region of Pará. Specimens of várzea area collected in the Igarapé do Costa community were used for analysis Urucurituba and Santa Maria do Tapará in Santarém, Pará, and specimens of non-flooded areas from the Floresta Nacional do Tapajós in Belterra (Florestal), Alter do Chão (Savana), Santarém and Jatuarana (Degradada) communities in Oriximiná, Pará. We analyzed 107 adult specimens of Bothrops atrox, 54 males and 53 females, comprising 53 specimens of várzea and 54 of non - flooded forests. Data collection was carried out by means of photos of the dorsal region and right side of the head of all the specimens, and analyzed from the ImageJ 1.46 software. In addition, venom glands were weighed on precision scales individually. The variables (except gland weight) were represented by the residuals of linear regression models, used to reduce the effects of body size (face-cloacal length) of snakes. A non-parametric Kruskal-Wallis analysis, complemented with Dunn's post hoc test, was used to analyze the morphometric differences presented by B. atrox specimens among habitats, while a Principal Component Analysis (PCA) was performed for decrease the dimensionality of the data, producing a smaller number of variables to represent the variations between the groups. The morphometric analyzes in the head of B. atrox of this study showed significant differences in seven of the 14 variables analyzed. Differences in the width and area of the head and venom glands were shown, as well as differences in weight of venom glands. All variations were between wetland and non-wetland specimens. These findings are possibly related to the different types of prey available in these habitats, despite the scarcity of studies on the diet of this species in lowland areas. Therefore, in this study, flooded forests pitviper presented smaller head size, as well as smaller and lighter venom glands in relation to the specimens of the other sampled habitats (Forest, Savanna and Degraded), demonstrating an intraspecific variation in head morphology among specimens of B. atrox of different habitats of the western region of Pará.